Monitoring your Fleets on the Go with RTDFMS [Real time distributed Fleet Monitoring System] - Kulkarni, Dr R B (International Journal of Advanced Science and Technology, 2019)
Fleets are an indispensable part of human life starting from an early phase.  There was always the need for a good carrier whether it was Stone Age or the age of modernized advanced technology of today.  Sheep’s and mules are still the means of transportation in the remote hilly areas where there is no facilitation of good transportation by roads. However, in recent the means of transportation and communication has been evolved so abruptly that almost none of the area is left where we do not have vehicles.Vehicles have touched every part of life. Whether it is the school bus which drops or carries your children or your daily schedule of life - going to Office, visiting relatives or buying goods for daily usages, no part of life is left untouched of it.  All because of this, the number of means of transportation are increasing day by day. More than 1.2 billion vehicles are running currently on the road at a time and so as the minimum number of peoples riding the vehicle. So in this contrast, for a public fleet servicing organization or any corporate organization, it has become mandatory to keep concern for the safety of peoples and their lives. For private organizations and companies, tracking of fleets have become mandatory in order to make the productivity of workers smoother and trustworthy..